Archiving Malaysian Popular Print Artefacts Through Digital Technology - Abd Rahman, Zainurul Aniza (2015)
Since Malaysia independence, not many of part of the domain of popular print such as magazines, newspapers, comic books, etc., are recorded or stored extensively in the national archives or libraries. They are not accorded significance as historical records in Malaysia. Only in the beginning of 2010, the archiving of the popular print culture such as magazines and cartoons began to be collected but the collections only started mainly from 1990s. In some other countries, the popular print artefacts have gained recognition as important cultural artefacts and have been allocated their own space in libraries, national archives, and even in some museums. This is because, through this historical print artefact, queries about the cultural histories and social evolutions may be discussed and answered. Preserving and archiving the popular print artefacts is a challenge in Malaysia. As pop-print artefacts are mainly considered as ephemeral artefacts, most of the early print have gone ‘disappeared’ and are not able to be retrieved even in the publisher’s resource centre. Scholarly communities, concern citizens, publisher and personal collectors are now began to engaged in the efforts to resolve the problems associated in preserving these artefacts in another kind of common resource: digital archiving.